Test Bank for Weiten and Lloyd's Psychology applied to modern life - Valentino, Mary Ann (Thomson/Wadsworth, 2006)
Filled with comprehensive, balanced coverage of classic and contemporary research, relevant examples, and engaging applications, Weiten and Lloyd's text shows students how psychology helps them understand themselves and the world, and uses psychological principles to illuminate the variety of opportunities they have in their lives and their future careers. While professors cite this best-selling book for its academic credibility and the authors' ability to stay current with ''hot topics,'' students say it's one text they just don't want to stop reading. Students and instructors alike find the text and associated workbook to be a highly readable, engaging, visually appealing package that provides a wealth of material they can put to use every day